Developing skills for employability with German Partners : 8 success stories from Southeast Asia - Niediek, Silvia [Verfasser] (Bundesinstitut für Berufsbildung, 2014)
"Each of the 'Developing Skills for Employability with German Partners' brochures presents eight vocational education and training success stories of German and international partners in various countries and regions. This brochure presents eight success stories of skill development in a joint effort by partners from Germany and Southeast Asia. With its wide range of tranining offers and its strong emphasis on employability , 'Training - Made in Germany' has the potential to succesfully contribute to the design process of the training systems in Southeast Asia via cooperation projects between partners from Southeast Asia and Germany." (BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; I 2.3.4 Asien; Berufsbildung; Internationale Zusammenarbeit; Bundesrepublik Deutschland; Südostasien